2017
DOI: 10.1186/s13046-017-0553-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of NLRP3 inflammasome in 5-fluorouracil resistance of oral squamous cell carcinoma

Abstract: Background5-Fluorouracil (5-FU) is a widely used drug for the therapy of cancer. However, the chemoresistance of tumor cells to 5-FU usually limits its clinical effectiveness. In this study, we explored the role of NLRP3 inflammasome in 5-FU resistance of oral squamous cell carcinoma (OSCC).MethodsThe mRNA and protein expression levels of NLRP3, Caspase1 and IL-1β in resected OSCC specimens or cell lines were measured respectively by quantitative real time-PCR (qRT-PCR) and western blot. NLRP3 and Ki-67 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 46 publications
3
103
0
Order By: Relevance
“…Recently, Zhang et al () reported that miR‐22 could be considered as both a predictor of 5‐FU sensitivity for personalized treatment and a therapeutic target for colorectal cancer (Zhang et al, ). As we previously revealed that the high expression and activation of NLRP3 inflammasome mediated the chemoresistance of OSCC cells to 5‐FU‐based therapy (Feng et al, ), we speculated that it was probably due to the downregulated expression of miR‐22.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Zhang et al () reported that miR‐22 could be considered as both a predictor of 5‐FU sensitivity for personalized treatment and a therapeutic target for colorectal cancer (Zhang et al, ). As we previously revealed that the high expression and activation of NLRP3 inflammasome mediated the chemoresistance of OSCC cells to 5‐FU‐based therapy (Feng et al, ), we speculated that it was probably due to the downregulated expression of miR‐22.…”
Section: Discussionmentioning
confidence: 89%
“…As the tumor model closest to the actual conditions of the human body, the PDX model can provide personalized drug guidance for a single patient and realize precision therapy for a tumor. In the field of OSCC research, xenograft OSCC mouse models are used for screening drugs(137)(138)(139) and studying drug resistance, such as cisplatin (9, 140), 5-fluorouracil(141), and cetuximab(142).…”
mentioning
confidence: 99%
“…It is interesting to nd that OSCC cells could secrete pro-in ammatory cytokines (such as IL-1β) and be in uenced by microbiota or their cell components, which indicates a more complex interaction between cancer cells, immune cells and microbiota in tumour microenvironment. Another report from our lab revealed that NLRP3 in ammasomeactivated IL-1β promoted 5-FU resistance in OSCC both in vitro and in vivo [29], and combining these data, it can be inferred that the presence of C. albicans in oral cancer may in uence the effect of chemotherapy by inducing IL-1β production, which was also a potential target for treating oral cancer.…”
Section: Discussionmentioning
confidence: 56%